ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN BERBASIS AKRUAL DI KABUPATEN BANGLI - Karyogis, Kadek Nila; Putra, I Pande Dwiana (E-Jurnal Akuntansi; Vol 20 No 1 (2017), 2017)
Accrual-based government accounting standards have been applied simultaneously in Indonesia since the enactment of Government Regulation No. 71 of 2010. However, in practice not all areas are ready to immediately adopt it, which one is Bangli. Unpreparedness of implementation is partly due to the lack of human resource competencies, organizational commitment and utilization of information technology. This study aimed to determine the effect of human resource competencies, organizational commitment and utilization of information technology at the level of implementation of accrual based government accounting standards. The research location is in SKPD Bangli regency. The method of analysis used is multiple linear regression. The sample was an employee of the financial administration already Civil Servants, and served at least one year. The results showed that the variables of human resource competencies, organizational commitment and utilization of information technology a positive effect on the level of implementation of accrual-based government accounting standards.
Keywords: Human Resource Competencies, Organizational Commitment and Utilization of Information Technology, Accrual-based Government Accounting Standards